HUMANISTIC APPROACH IN THE DEVELOPMENT OF ISLAMIC EDUCATION CURRICULUM - Sofwatun Nida; Putri Nadha Setyaningrum; Tasman Hamami; Arif Zefrizen (Institut Binamadani Indonesia, 2026)
Islamic Religious Education (PAI) experiences various problems in its learning process. The current implementation of the PAI curriculum is still insufficient in helping to develop the potential of students. The PAI learning process has not been able to fully develop all aspects of individual student potential. There are still many learning processes carried out with the teacher as the center without involving existing students. The aim of this research is to analyze the theories and frameworks of humanistic approaches that are relevant in developing the PAI curriculum. The method used in this research is library research through a process of selection, search, presentation and analysis of library materials. The results of the research show that a humanistic approach that is integral, the role of the teacher is not authoritative, and cooperative learning in the development of the PAI curriculum provides a new perspective on objectives, materials, methods and evaluation. Some implementations of the humanistic approach are student centered learning, humanizing of the classroom, quantum learning, accelerated learning and active learning. The humanistic approach is not free from criticism, but if used correctly and according to needs, it can be used in developing the PAI curriculum to develop the potential of students.